Investigating the element distribution of argumentative essay and its quality: The case of Indonesian EFL students - Nirwanto, Rahmadi; Mukminatien, Nur; Suryati, Nunung; Wulyani, Anik Nunuk (Journal on English as a Foreign Language, 2024)
Although many research studies discussed argumentative essays, little is known about argumentative essays discussing the dialogical exchange of argumentation. This study aims to investigate the distribution of elements and the quality of argumentative essays produced by EFL students. The content analysis was employed to examine their argumentative essays. The data were garnered from essay writing tests for forty students of the English Department at a state university in Palangka Raya, Indonesia. They were assigned to write an argumentative essay about "Online learning during the COVID-19 pandemic.” The data analysis comprised collecting, categorizing, and displaying the data and conclusion drawing. The results indicated that (1) a greater number of the students were not able to supply all elements of an argumentative essay, such as an explanation of an issue, thesis statement, counterargument, refutation, and conclusion, and (2) most of them failed to obtain excellence qualification. The study findings imply how teachers can redesign the materials, find effective strategies for teaching an argumentative essay, and provide many practice opportunities. The teachers should focus on teaching an argumentative essay element by allowing the students to understand the goal of each element and integrate them to form a well-developed argumentative essay.